Problems in the Application of Law in the Indra Kenz Fraudulent Investment Case - Alamsyah, Feiruz Rachmita; Cameron, Calvin; Ridwan, Piero; Yustisia, Muhammad Tio; Romadhon, Moh. Rahmat Rizki; Yusuf, Natasya Thufailah (The Digest: Journal of Jurisprudence and Legisprudence, 2023)
Fraudulent investment, also known as fake investment, is one of the most serious problems in Indonesia. One of the most famous cases of fraudulent investment is the case of Indra Kenz, a young entrepreneur who ran a fraudulent investment business that defrauded thousands of people. This article aims to analyze Indra Kenz's fraudulent investment case from a legal perspective using the normative juridical research method. Data is obtained from literature study and analysis of documents related to Indra Kenz's case. The results of the analysis show that Indra Kenz's fraudulent investment practices violated a number of laws and regulations in Indonesia, such as Law No. 8 of 2010 on the Prevention and Eradication of Money Laundering. In addition, the practice also violated fundamental legal principles, such as the principles of justice and trust. Indra Kenz's case is a valuable lesson for the public and the government to be more vigilant against fraudulent investment practices. The government needs to improve supervision and provide strict sanctions for fraudulent investment actors to prevent similar cases from occurring in the future.